The Data Journalism Practices in the Production of Investigative News Videos by Narasi TV - Intan Fajarlie, Nadia; Muda Z. Monggilo, Zainuddin (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The digital and open data era has given rise to the development of methods in data journalism to create an in-depth or investigative news report. The widespread use of social media, dominated by the Y and Z generations, has also encouraged journalists to present the story in attractive formats. As one of the digital media in Indonesia, Narasi TV has data-based long-form stories called Buka Mata, presented in video forms and published through various social media. This research aims to answer the question, “How does Narasi TV produce the data journalism videos in Buka Mata?” to describe Narasi TV’s data journalism practices. This study uses a constructivist paradigm, a qualitative approach, and the case study method; and refers to the data journalism concept from The Data Journalism Handbook in 2012 to solve the research question. The findings show that Narasi TV has implemented data journalism practices such as gathering, verifying, analyzing, and visualizing data in producing Buka Mata. Furthermore, Narasi TV also uses an open-source intelligence (OSINT) method to create its investigative news videos.